2019
DOI: 10.1177/0956797619893062
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting a Fatal Decision: Direct Replication of the Predictive Validity of the Suicide–Implicit Association Test

Abstract: A previous study by Nock et al. (2010) suggested that people’s implicit identification with “death” or “suicide” can accurately predict whether they will attempt suicide several months in advance. We report the first direct and independent replication of this promising finding. Participants were 165 patients seeking treatment at a psychiatric unit in France. At baseline, patients completed the Suicide–Implicit Association Test (S–IAT), a semistructured interview, and a self-report measure of suicide ideation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
3
24
2
Order By: Relevance
“…To summarize, contrary to previous studies (Barnes et al, 2017;Nock et al, 2010;Tello et al, 2020), our results do not suggest that implicit measures predict suicide behavior, whether planning or an actual attempt. Yet, important differences between previous studies and the current study need to be pointed out.…”
Section: Summary Of Findingscontrasting
confidence: 99%
See 4 more Smart Citations
“…To summarize, contrary to previous studies (Barnes et al, 2017;Nock et al, 2010;Tello et al, 2020), our results do not suggest that implicit measures predict suicide behavior, whether planning or an actual attempt. Yet, important differences between previous studies and the current study need to be pointed out.…”
Section: Summary Of Findingscontrasting
confidence: 99%
“…Previous studies showed that the Death IAT can be used to predict suicide attempts in the long term (Barnes et al, 2017;Nock et al, 2010;Tello et al, 2020). In this study, we set out to investigate a longer follow-up period (18 months), test a wider range of implicit methods (three IATs and a subliminal priming task), and report multiple outcomes in regard to suicidality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations